Single-center experience in kidney transplantation: outcomes, conclusions, and perspectives - M. Sh. Khubutia; I. V. Dmitriev; A. G. Balkarov; Yu. A. Anisimov; N. V. Shmarina; N. V. Zagorodnikova; N. V. Borovkova; M. G. Minina; D. V. Lonshakov; V. O. Aleksandrova; V. Smirnova; A. U. Rustambek (Вестник трансплантологии и искусственных органов)
Kidney transplantation (KT) remains the best treatment for patients with chronic kidney disease (CKD) stage 4–5. It helps patients live longer, have better quality of life, and undergo improved medical and social rehabilitation. This paper examines the outcomes of KT performed between 2019 and 2023.Materials and methods. There were 1,106 KTs deceased donor KTs performed between January 1, 2029, and December 31, 2023. The recipients had a median age of 45 (37–54) years, with 664 (60%) males and 442 (40%) females. Donors were mainly males (n = 706, 63.8%), with the median donor age being 50 (43–57) years. Induction immunosuppressive therapy (IST) with monoclonal antibodies was administered to 859 (77.7%) recipients, with polyclonal antibodies to 122 recipients (11%), and induction without antibodies to 125 recipients (11.3%). Triple-drug baseline IST consisted of a combination of calcineurin inhibitors, antimetabolites and glucocorticoids. Tacrolimus was the most often utilized calcineurin inhibitor (n = 961, 86.9%), while cyclosporine was used less often (n = 145, 13.1%). Mycophenolic acid (n = 1041, 94.1%) was used as the second medication in most recipients, while everolimus (n = 54, 4.9%) and azathioprine (n = 11, 1%) were used less often.Results. Primary initial renal graft function was noted in 714 patients (64.6%) and delayed in 392 recipients (35.4%). Overall incidence of surgical complications was 11.6% (n = 130), and immunological complications 9.9% (n = 109). At hospital discharge, 768 recipients (69.4%) had satisfactory kidney allograft (KAG) function, while 276 recipients (25%) were discharged with graft dysfunction; median serum creatinine and blood urea levels were 158 (120–204) μmol/L and 11 (8–16) mmol/L, respectively. Twenty-six recipients (2.4%) were discharged to continue renal replacement therapy; 28 recipients (2.6%) underwent in-hospital graft nephrectomy. Twelve individuals passed away during the hospitalization phase. The cumulative uncensored in-hospital graft and recipient survival rates were 97.5% (n = 1078) and 98.9% (n = 1094), respectively.Conclusion. KT is an effective and safe transplant modality for stage 4–5 CKD. Our KT outcomes are consistent with those of reputable transplant centers around the globe.